Development Of Quartz-Kaolin Separation Technology - M. Marinov (International Mineral Processing Congress, 2012)
The Bulgarian deposits of quartz-kaolin raw materials are localized in the NE Bulgaria. For many years, the quartz-kaolin sand separation has been performing by water washing technology. After wet separation the raw material yields two products ? washed kaolin (different grades) and quartz sand (different grades). Research and development program has started to improve the quartz-kaolin sand separation. The program has undertaken an increasing of processing capacity, to decrease the losses in the tailings and to provide production of new quartz sand grades. The kaolin-silica raw materials from Vetovo open mine and the technological tailings from Vetovo processing plant were characterized. It was established that there are a lot of losses of quartz in final tailings. New approach on kaolin-silica raw material separation was tested in laboratory scale. The test work was performed on Derrick Stacksizer screening machines. The results of laboratory experiment show that there are possibilities to increase the quartz sand recovery and to start the production new grade sand. The full-scale pilot test was performed including the following units: two Derrick Stacksizer screening machines equipped with 0.430 mm and 0.150 mm opening Derrick Urethane Panel, respectively; Flat bottom DN 500 Hydrocyclone and DN 100 Hydrocyclon. The pilot test data clearly demonstrate that the Derrick Stacksizer screening machines are suitable for Bulgarian silica-kaolin raw material. Based on the test data a new quartz-kaolin separation technology was developed. The new technology was introduced in Vetovo processing plant increasing processing capacity and decreasing the losses of quartz in final tailings. Additionally the production of silica sand grade PK 0.16 is increased and starts the production a new grade PK 0.10.